The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/2645607
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Idiopathic Premature Ovarian Failure by Color Doppler Ultrasound under the Intelligent Segmentation Algorithm

Abstract: The aim of this study was to explore the application value of transvaginal color Doppler ultrasound based on the improved mean shift algorithm in the diagnosis of idiopathic premature ovarian failure (POF). In this study, 80 patients with idiopathic POF were selected and included in the experimental group, and 40 volunteers who underwent health examinations during the same period were selected and included in the control group, who underwent transvaginal Doppler ultrasound examination. At the same time, an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…9 Through the use of post-processing software, list marking processing can be implemented for different follicle diameters and volumes, which is convenient for clinicians to observe the subtle follicular structural changes and improves analysis of sinus follicle development. Yu L et al 12 16 This study shows that transvaginal threedimensional ultrasound has good diagnostic efficacy for both DOR and POF, which is consistent with the results of Singhal P et al 19 The use of 3D-TVS technology in the diagnosis and evaluation of DOR and POF does have application value. 15,18 With the progress and update of the examination equipment, ultrasound technology is simple, fast, non-invasive and accurate, and has been gradually cited in clinical work.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…9 Through the use of post-processing software, list marking processing can be implemented for different follicle diameters and volumes, which is convenient for clinicians to observe the subtle follicular structural changes and improves analysis of sinus follicle development. Yu L et al 12 16 This study shows that transvaginal threedimensional ultrasound has good diagnostic efficacy for both DOR and POF, which is consistent with the results of Singhal P et al 19 The use of 3D-TVS technology in the diagnosis and evaluation of DOR and POF does have application value. 15,18 With the progress and update of the examination equipment, ultrasound technology is simple, fast, non-invasive and accurate, and has been gradually cited in clinical work.…”
Section: Discussionsupporting
confidence: 86%
“…11 These difference may be due to the fact that the inflow site of the right ovarian vein is the inferior vena cava, while the inflow site of the left ovary is the left renal vein. 11,12 Currently, there are few clinical comparative analyses of the left and right ovaries using three-dimensional ultrasound, and further discussion is warranted. 13,14 Our results reported lower AFC, OV, VI, VFI and FI within both the DORgroup and the POF-group versus the Normal ovarian function group (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the customized risk of POI following chemotherapy, Chung et al constructed a machine learning-based model that had an accuracy of 88% (area under the ROC 0.87, 95% CI: 0.77-0.96; p < 0.001) (96). An enhanced mean shift algorithm based on artificial intelligence (AI) technology was used to process ultrasound images in women with idiopathic POI, where the functional condition and hemodynamics of patients' ovaries were clearly visible on the transvaginal color Doppler ultrasonography (97). Another study demonstrated that building diagnostic methods for POI prediction may be accomplished using artificial neural networks, where the generalization ability of the train set, validation set, and test set was validated, with a prediction accuracy of over 90% in the test, train, and validation sets (98).…”
Section: Premature Ovarian Insufficiencymentioning
confidence: 99%
“…Ultrasonography has an important role in reproductive medicine and assisted reproductive technologies because of its utility for several purposes including ovarian response monitoring, assessment of endometrial receptivity, transvaginal aspiration of oocytes, transcervical transfer of the embryo to the uterus, pregnancy monitoring, and fetal health assessment. It is also used to measure ovarian volume, antral follicular count (AFC), ovarian stromal blood flow, and to evaluate ovarian function after vascular embolization (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%